Optimasi kondisi proses pengeringan ampas wortel menggunakan RSM dan pemanfaatannya sebagai masker gel peel off - Asri Widyasanti; Tiara Namira; Sarifah Nurjanah (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Carrot pulp is a by-product of juice production with a source of pectin and carotene precursors of vitamin A. One way to use carrot pulp is through a drying process, such as convection drying, to produce carrot pulp flour. The purpose of this study was to determine the optimal conditions for drying carrot pulp using a food dehydrator, to determine the characteristics of carrot pulp powder under optimal conditions, and to determine the potential of carrot pulp powder in preparing peel off gel masks. The parameters in this study were moisture content, ash content, and drying yield. In addition, the parameters observed in the optimum carrot pulp flour were color and antioxidant activity. The dryer used was a food dehydrator operating at a temperature range of 45°C to 65°C for a duration of 20 to 26 hours. This research method was an experimental method with optimization using the Response Surface Methodology (RSM) type Central Composite Design (CCD) in the Design Expert 13 application. RSM determined the optimal drying process condition to be 65°C for 26 hours. This condition resulted in a product with a moisture content of 3.033%, an ash content of 5.326% and a drying yield of 11.062%. Carrot pulp flour produced under optimal drying conditions, when formulated into a peel off gel mask preparation, exhibited a drying time of 15-21 minutes.